2019
DOI: 10.1080/13621718.2019.1637172
|View full text |Cite
|
Sign up to set email alerts
|

Observation and analysis of metal transfer phenomena for high-current super-TIG welding process

Abstract: Super-TIG welding is a newly developed TIG welding process using C-type filler metal in TIG welding. In Super-TIG welding, C-filler can prevent the molten pool depression, which is caused by high pressure in the center of the arc during high current TIG welding. In this study, metal transfer modes for C-type filler metal were observed. During these observations, feeding heights were varied for the current of 430 A. It was observed that the stable and continuous bridging transfer along with the arc blow on fill… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
6
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9
1

Relationship

3
7

Authors

Journals

citations
Cited by 19 publications
(6 citation statements)
references
References 19 publications
0
6
0
Order By: Relevance
“…Among them, pulsed current GTAW showed refined grain structure, high toughness, and joint strength. 21,22 Later, the studies identified that reducing the welding area by a narrow gap reduces the multi-pass heat input to the welded joint. The narrow gap welding using GTAW welding showed significant improvements in the prevention of cracking and the yield strength to tensile strength ratio.…”
Section: Introductionmentioning
confidence: 99%
“…Among them, pulsed current GTAW showed refined grain structure, high toughness, and joint strength. 21,22 Later, the studies identified that reducing the welding area by a narrow gap reduces the multi-pass heat input to the welded joint. The narrow gap welding using GTAW welding showed significant improvements in the prevention of cracking and the yield strength to tensile strength ratio.…”
Section: Introductionmentioning
confidence: 99%
“…One of the solutions to these problems is the automation of the welding process and the possibility of using welding speeds much higher than those in the manual process. As a result of automation, an increase in the repeatability of welding production is observed, as well as an increase in efficiency with a reduced amount of heat input into the material [14][15][16][17][18][19][20]. The use of automated welding processes also makes it possible to change the method of preparing the edges for welding, as in manual welding the groove (bevel) must be wide so that the welder can reach the arc and observe the weld pool, and for the automated process it is unnecessary.…”
Section: Introductionmentioning
confidence: 99%
“…1) The main limitation in TIG welding is the maximum depth of penetration in a single pass which leads to joining thick sections with multi passes. 3) In TIG, welding fluxes are not used because of the formation of slag, causing corrosion on weld metals. Further welding current is another factor affecting the weld joint.…”
Section: Introductionmentioning
confidence: 99%